Improving the quality of dry-cured sausages using pork from rustic breeds - Banon, Sancho; Bedia, Mario; Almela, Elisabeth; Martinez, Pedro Jose (MTT Agrifood Research Finland, 2010)
The use of pork from rustic pig breeds was tested to improve the quality of dry-cured fermented sausages. The quality of a salchichon/salami-type sausage manufactured with pork from Chato Murciano breed (CM) and Early White pig (EW) (Large White ~ Landrace breed) was compared. CM pork improved several quality characteristics of dry-cured fermented sausage. Significant (p . 0.05) differences between mean CM and EW values were found for total lipids, ash, collagen, water activity, total acidity, CIELab colour, proteolysis, fat acidity, fatty acid profile, total viable counts, lactic acid bacteria, Micrococacceae, moulds and yeasts, colour, odour, flavour, fattiness and acceptance. CM mainly intensified the reddening of sausage cuts and increased monounsaturated acids in fat. Acceptance was also better for CM, although odour and flavour were only slightly improved. The production of high-quality specialities of dry-cured meat products can contribute to the sustainable production of CM and similar rustic pig breeds, maintaining the genetic diversity of pig species.
Keywords: Chato Murciano; pig; salchichón; salami; ripening; eating quality